Comparative efficacy of seven Chinese patent medicines for early diabetic kidney disease: A Bayesian network meta-analysis. (August 2022) - Zhao, Jie; Ai, Jun; Mo, Chao; Shi, Wei; Meng, LiFeng
Abstract: Background: Bailing Capsule (BLC), Jinshuibao (JSB), Huangkui Capsule (HKC), Uremic Clearance Granule (UCG), Tripterygium glycosides (TG), Compound Xueshuantong Capsule (CXC), and Shenyan Kangfu Tablet (SYKFT) as classic Chinese patent medicines (CPMs), have been widely used and shown beneficial effects on the treatment of early diabetic kidney disease (DKD). However, the comparative efficacy of seven CPMs in the treatment of early DKD remains unknown. Objective: To evaluate and compare the efficacy of seven CPMs (BLC, JSB, HKC, UCG, TG, CXC, SYKFT) combined with angiotensin-converting enzyme inhibitor (ACEI) or angiotensin receptor blocker (ARB) on early DKD by a Bayesian network meta-analysis (NMA) of randomized controlled trials (RCTs). Methods: A comprehensive and systematic literature search was performed in PubMed, Embase, Cochrane Library, Web of Science, Clinical Trials.gov, China Biology Medicine, Chinese National Knowledge Infrastructure, Chinese Scientific Journal, and Wanfang databases from inception to March 14, 2021, for full-text RCTs that evaluated the efficacy of seven CPMs combined with ACEI/ARB on patients with early DKD. Two reviewers independently screened studies for eligibility, extracted data, and assessed the risk of bias. Agreement between reviewers was measured using kappa statistics. Mean difference (MD) and odds ratio (OR) were calculated to evaluate continuous variables and dichotomous, respectively. The random effect modeling NMA was performed and the ranking probability of interventions in various outcomes was also conducted based on the surface under the cumulative ranking curve (SUCRA). Begg's and Egger's tests were used to evaluate publication bias. The certainty of the evidence for outcomes was evaluated according to the GRADE system. Results: A total of 62 RCTs with 5362 patients with early DKD were identified. The value of Kappa calculated for the various parameters extracted by the two investigators was 0.821 ( P  < 0.001). Among these CPMs, UCG + ACEI/ARB showed the best effectiveness for urinary albumin excretion rate (UAER) (MD 32.25, 95% CrI 19.11–45.67, low certainty) with SUCRA 92%. JSB + ACEI/ARB showed the highest effectiveness for 24-h urinary total protein (24-h UTP) (MD 76.92, 95% CrI 53.54–100.58, low certainty) with SUCRA 97%. CXC + ACEI/ARB showed the highest effectiveness for serum creatinine (SCr) (MD 26.02, 95% CrI 6.10–45.95, low certainty) with SUCRA 96%. HKC + ACEI/ARB showed the highest effectiveness for blood urea nitrogen (BUN) (MD 1.46, 95% CrI 0.42–2.54, very low certainty) with SUCRA 86%. BLC + ACEI/ARB showed significant differences in triglyceride (TRIG) (MD − 1.17, 95% CrI − 1.93 to − 0.43, low certainty) with SUCRA 90%, total cholesterol (TC) (MD − 1.17, 95% CrI − 1.97 to − 0.39, very low certainty) with SUCRA 90%, and C-reaction protein (CRP) (MD − 0.90, 95% CrI − 1.51 to − 0.32, very low certainty) with SUCRA 76%. Conclusions: CPMs + ACEI/ARB might be positive efficacious interventions from which patients with DKD will derive benefit. UCG + ACEI/ARB, JSB + ACEI/ARB, CXC + ACEI/ARB, and HKC + ACEI/ARB might be potentially the preferred intervention for reducing UAER, 24-h UTP, SCr, and BUN levels, respectively. BLC + ACEI/ARB has a better impact on lowing TRIG, TC, and CRP levels in patients with early DKD. However, more high-quality, large-scale, multi-center RCTs and stronger head-to-head trials are required to confirm these findings. Highlights: Diabetic kidney disease (DKD) is one of the most common microvascular complications of diabetes. There is a lack of head-to-head comparisons efficacy between different Chinese patent medicines (CPMs) on early DKD. CPMs + ACEI/ARB might be positive efficacious interventions from which patients with DKD will derive benefit. High-quality, large-sample, multi-center RCTs and head-to-head comparative evidence are needed to confirm these findings.